2007
DOI: 10.1292/jvms.69.1179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of Recovery from Total Intravenous Anesthesia with Propofol and Inhalation Anesthesia with Isoflurane in Dogs

Abstract: ABSTRACT. The characteristics of recovery from total intravenous anesthesia (TIVA) with propofol and inhalation anesthesia with isoflurane was clinically compared in 149 client-owned dogs that anesthetized for surgical or diagnostic procedures. In all dogs, anesthesia was induced with an intravenous injection of propofol following premedication with acepromazine or diazepam. As a result, 58 dogs anesthetized with propofol-TIVA showed slower but smoother recovery than 91 dogs anesthetized with isoflurane anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
0
25
0
5
Order By: Relevance
“…TSAI et al (2007) demonstrated that 89.7% of the dogs anesthetized with a continuous infusion of propofol showed an excellent recovery without any signs of excitement or vocalization. However, opisthotonus was observed in two animals in the EMU group after the infusion ceased, lasting approximately 10 minutes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…TSAI et al (2007) demonstrated that 89.7% of the dogs anesthetized with a continuous infusion of propofol showed an excellent recovery without any signs of excitement or vocalization. However, opisthotonus was observed in two animals in the EMU group after the infusion ceased, lasting approximately 10 minutes.…”
Section: Resultsmentioning
confidence: 98%
“…Transient signs of neurologic excitement during or after propofol administration have been reported, including opisthotonus (TSAI et al, 2007). According to BEVAN (1993), propofol seems to have an antagonistic effect on spinal aminoacid glycine and strychnine receptors, which could explain the opisthotonus and the myoclonus.…”
Section: Resultsmentioning
confidence: 99%
“…Este método de anestesia promove estabilidade hemodinâmica, em associação à fácil manutenção do plano anestésico e a recuperação suave e tranquila (Beths et al 2001, Tsai et al 2007, Galante et al 2014, Chang et al 2016. As doses que foram utilizadas, tanto para indução quanto manutenção, estão dentro da mesma faixa empregada em canídeos domésticos (Mannarino et al 2014).…”
Section: Discussionunclassified
“…Tsai et al. [27], when comparing dogs’ recovery from anesthesia maintained with isoflurane or propofol, found that the isoflurane-maintained group stood more quickly than the propofol-maintained group (mean time 27.7 vs. 34.5 min), even though the incidence of adverse effects was not different.…”
Section: Discussionmentioning
confidence: 99%